2015
DOI: 10.1007/s00227-015-2634-8
|View full text |Cite
|
Sign up to set email alerts
|

The importance of sampling design: spatial patterns and clonality in estimating the genetic diversity of coral reefs

Abstract: demonstrate by rarefaction analysis that the bias in estimating clonal richness (i.e., the proportion of unique genotypes in a given sampling area relative to the total number of samples surveyed) for small sample numbers is due to the predominance of clones (i.e., high level of clonality) and not skew in genet frequency distribution. Overall, we argue that: (1) consideration of sampling design is important in population genetic studies, particularly since non-random sampling in the presence of SGS can give bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
(80 reference statements)
1
22
0
Order By: Relevance
“…The genotype diversity (>1,000 genotypes) observed in this study is the highest ever documented for terrestrial or marine populations. Most studies assessing genetic variation in partially clonal organisms are not spatially explicit (Arnaud‐Haond et al., ; Gorospe, Donahue, & Karl, ; Schwartz & McKelvey, ), are based on sampling few individuals (~50) (Adjeroud et al., ; Ardehed et al., ; Becheler, Benkara, Moalic, Hily, & Arnaud‐Haond, ) or involve sampling of a single habitat (Gorospe & Karl, ). Such studies may therefore underestimate genotype diversity in clonal populations.…”
Section: Discussionmentioning
confidence: 99%
“…The genotype diversity (>1,000 genotypes) observed in this study is the highest ever documented for terrestrial or marine populations. Most studies assessing genetic variation in partially clonal organisms are not spatially explicit (Arnaud‐Haond et al., ; Gorospe, Donahue, & Karl, ; Schwartz & McKelvey, ), are based on sampling few individuals (~50) (Adjeroud et al., ; Ardehed et al., ; Becheler, Benkara, Moalic, Hily, & Arnaud‐Haond, ) or involve sampling of a single habitat (Gorospe & Karl, ). Such studies may therefore underestimate genotype diversity in clonal populations.…”
Section: Discussionmentioning
confidence: 99%
“…Even using relatively large sample sizes (from 100 to 500 individuals) leads to deeply biased estimates of the true R and and thus c values. R is always greatly overestimated, by some orders of magnitude more than previously demonstrated with empirical datasets for which the rates of clonality remained unknown (Arnaud-Haond et al 2007;Gorospe et al 2015), and except in nearly strictly sexual populations, was also greatly overestimated (for c ≥ 0.1).…”
Section: Detecting Clonality Under Realistic Conditionsmentioning
confidence: 67%
“…; Gorospe et al 2015). These two studies demonstrated this worrying effect by using two empirical datasets (of seagrasses and corals) where the true rates of clonality were unknown;…”
mentioning
confidence: 99%
“…In the present paper, Gorospe et al (2015) demonstrate that spatial genetic structure within reefs should be a concern to coral geneticists seeking to describe genetic diversity either within reefs or between reefs (that is, to estimate population genetic structure or gene flow). Moreover, for a number of realistic scenarios, they show that the power to detect small-scale positive spatial autocorrelation is quite low; thus, failure to detect a spatial autocorrelation pattern will not constitute strong evidence for the absence of such a pattern.…”
mentioning
confidence: 82%
“…Although the emphasis of Gorospe et al (2015) is on corals, intriguingly the authors suggest that positive spatial autocorrelation at short distances might be common in marine organisms, albeit subtle and difficult to detect. Positive spatial autocorrelation at very small distances (<100 m) has been reported for a number of marine taxa, notably those low dispersal ability (e.g., seagrasses: Alberto et al 2005;Migliaccio et al 2005;Ruggiero et al 2005, sponges: Calderon et al 2007Blanquer et al 2009, bryozoans: Pemberton et al 2007, and ascidians: Yund and O'Neil 2000David et al 2010), but whether positive spatial autocorrelation at relatively short distances is also common for taxa with extended larval durations is unknown.…”
mentioning
confidence: 99%